1997
DOI: 10.1021/jf9706641
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Levels of Residual Nitrite in Canadian Cured Meat Products over the Past 25 Years

Abstract: Nitrite is used widely as a preservative in the processing of cured meat products mainly for its antimicrobial properties against Clostridium botulinum. There is concern, however, over nitrite's role in the formation of various N-nitroso compounds in such products and for a suggested link between consumption of cured meats and incidence of childhood leukemia and brain tumors. The objective of this study was to obtain current data on residual nitrite levels in Canadian cured meat products that will be useful fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…The blends have a pH of 7.0, whereas sodium tripolyphosphate has a pH of 9.7; blends also have strong buffering capacity. The residual nitrite values reported in this study, after 49 d (same period as usual sale of commercial wieners), were higher than the values reported by Cassens (1997); however, they were close to the values reported by Sen and Baddoo (1997). Reasons for this difference might be a lower heat treatment, a higher initial nitrite concentration (156 ppm, meat basis), difference in storage time and temperature, and…”
Section: Resultssupporting
confidence: 61%
“…The blends have a pH of 7.0, whereas sodium tripolyphosphate has a pH of 9.7; blends also have strong buffering capacity. The residual nitrite values reported in this study, after 49 d (same period as usual sale of commercial wieners), were higher than the values reported by Cassens (1997); however, they were close to the values reported by Sen and Baddoo (1997). Reasons for this difference might be a lower heat treatment, a higher initial nitrite concentration (156 ppm, meat basis), difference in storage time and temperature, and…”
Section: Resultssupporting
confidence: 61%
“…A similar tendency was registered for smoked sausages and ham products. Sen and Baddoo (1997) also reported decreases of NaNO 2 and NaNO 3 in US and Canadian originating meat products. The means of nitrite content of Canadian sausages in 1985 and 1996 were 34 and 26 mg kg À1 , respectively.…”
Section: Nitrites and Nitrates In Meat Productsmentioning
confidence: 81%
“…According to the results of Penttilä (1995), the mean concentrations of nitrate and nitrite in cooked sausages were 48 mg kg À1 (range 0-124 mg kg À1 ) and 32 mg kg À1 (1.4-53 mg kg À1 ), respectively. In Canada, the content of nitrites in sausages was 26 mg kg À1 (range 9-37 mg kg À1 ) and in ham 24 mg kg À1 (9-40 mg kg À1 ) (Sen and Baddoo 1997). In Estonia, the maximum permitted concentrations of residual nitrite (as NaNO 2 ) and nitrate (as NaNO 3 ) in commercial meat products are 100 and 250 mg kg À1 , respectively.…”
Section: Nitrites and Nitrates In Meat Productsmentioning
confidence: 99%
“…EFSA (2003) In Canada, Sen and Baddoo (1997) studied the data from official monitoring programs concerning nitrites levels in various meat products in 25 years time ). Keeton et al (2009) reported residual nitrites levels of 7 ppm in cured meat products (hot dogs, bacon and hams) from five cities of USA.…”
Section: Nitrates and Nitrites Content In Meat Productsmentioning
confidence: 99%